Engaging Collections: Libetshu in the Van Warmelo Collection, Ditsong National Museum of Cultural History, South Africa - Nzimela, Yola Siyamthanda (University of the Witwatersrand, Johannesburg, 2025)
This thesis broadly examines curatorial practice of African ritual material culture within museum and related institutional collections in South Africa. Specifically, I focus on divination material known as libetshu, or Mankgwanyana, heir looms, in the Nicolaas van Warmelo collection, the Ditsong National Museum of Cultural History, Pretoria, South Africa. Although many communities from which ritual objects such as these divination materials originate still revere them as sacred, there is a lack of meaningful inclusion of source communities in curatorial decision-making mainly due to elitist or Eurocentric perspectives on culture due to colonial legacies and/or where curatorial practices reside with Western trained professionals. Globally and locally, limited accurate archival contextual data about such divination material constrains connecting the objects to source communities. This thesis therefore sought to enhance understanding of libetshu /Mankgwanyana as ritually activated divination material, to encourage appropriate curation that takes cognisance of their spiritual significance for communities that hold them sacred. Through use-wear analysis, semi-structured interviews with traditional practitioners and curators, and a curatorial justice framework, I show that libetshu / Mankgwanyana are divination materials used in ritual performances, are spiritual and require specific handling and curation. I find that whilst co-curation with source communities and stakeholders is essential, a blanket approach for ritual objects is insufficient as each divination material belongs to different ancestral lineages. These findings highlight the importance of epistemic restitution and demonstrate the effectiveness of a curatorial justice approach that promotes sensitive, respectful, and appropriate curatorial practices cognisant of the integrity of divination materials such as libetshu / Mankgwanyana in collections.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2025
Keywords: Curation; Justice; Indigenous knowledge; Ethnological collections; Museums; Archives.; UCTD; SDG-4: Quality education; SDG-15: Life on land